Study of Some Chemical & Bacteriological Properties of Groundwater and its Suitability for Drinking in Qurji Region and the Western Street، Tripoli - Libya. - Mayouf, Karima; Sharif, Abubaker (Journal of Pure & Applied Sciences, 2024)
Providing drinking water suitable for human consumption is one of the most important challenges in Libya. This study aims to evaluate the suitability of drinking water for some wells in the Qurji and Western Street areas in Tripoli-Libya. Water samples were collected from (7) wells in the targeted area. This study includes some physical and chemical analyzes such as pH، electrical conductivity، TDS، Sodium، Potassium، Chloride، Sulfates، and Nitrate ions، in addition to bacteriological analyzes such as total number of Aerobic bacteria، total Coliform bacteria، and Escherichia coli bacteria. Results showed that the obtained pH values were in agreement with the range allowed by the WHO for drinking water، with the exception of well No. (1)، where the pH value was 6.24، which is less than the permissible rate. Electrical Conductivity values ranged from 45.8 to 4280 micro siemens. TDS values range (29.7−2840 mg/L) and Na، K، Cl، SO4، NO3 ions concentration range (1.39 − 255.7 mg/L)، (0.52 − 33.77 mg/L)، (0.9 − 5.5 mg/L)، (1 − 99 mg/L)، and (1.1 − 14.7 mg/L) respectively. As for bacteriological analyses، the samples were free of bacteria، with the exception of well No. 4، in which the numbers of total Coliform bacteria were more than 5,000 colonies per liter (500 per 100 ml). Thus، a comparison of the results obtained، the water samples studied (except the samples from wells No. 1 and 4) were in conformity with the Libyan standard specification for drinking water and are suitable for human consumption.